THE FALSE NARRATIVE OF SETTLER COLONIALISM PORTRAYED IN ISRAELI CHILDREN’S STORY BOOK - Indah Mustika Santhi (Universitas Gunadarma, 2025)
The false narrative of settler colonialism is a form of colonial narrative through literacy media carried out to be able to control an area and eliminate the identity of the indigenous population of a community. This study aims to dismantle the false narrative contained in one of the Israeli children's story books entitled “Alon and Lebanon